PENERAPAN PELAYANAN PRIMA DI PT. PANDI KENCANA MURNI PEKANBARU - Mika Yenti; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research titled The Application Excellent In PT. Pandi Kencana Murni Pekanbaru. This study aims: (1) to find out how the implementation of excellent service in PT. Pandi Kencana Murni Pekanbaru has been set according to the concept A4 excellent service, (2) know the obstacles in applying excellent service in PT. Pandi Kencana Murni Pekanbaru. The sampels used in this study were 73 people, the sampling technique was determined using accidental sampling technique, this study used a quantitative descriptive method to examine the issues raised in this study. This research was conducted in PT. Pandi Kencana Murni street Paus No 104 C Pekanbaru, the study was conducted for 6 month, starting from November 2019 – April 2020. The technique of collecting data using observation, documentation, interviews, and questioner. The sample of this research is umrah pilgrims who have used the services in PT. Pandi Kencana Murni Pekanbaru. The results of this study indicate that overall respondents gave very good responses to the excellent service provided by PT. Pandi Kencana Murni Pekanbaru pure, this is evidenced by results of a questioner from the responses of pigrims who have used the services in PT. Pandi Kencana Murni Pekanbaru with very good value. Excellent service is the most important value for a company engaged in services.Keywords: Service, Excellent Service, Travel Agency